Peran Orang Percaya dalam Menjaga Keamanan dan Ketertiban Bangsa: Suatu Tinjauan Teologis berdasarkan Perspektif Alkitab - Rumagit, Oksje M O; Rahayu, Sri (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
This study addresses the growing challenges of social conflict, intolerance, moral decline, and weak legal awareness that threaten national security and social order. It aims to examine the theological foundations of security and order from a biblical perspective and to analyze the role of believers as citizens in maintaining social stability within a pluralistic society. The research employs a qualitative descriptive method using a biblical-theological and hermeneutical approach. Data are collected through a literature review of biblical texts, theological writings, and relevant scholarly works, and analyzed using content analysis with contextual interpretation. The findings show that security and order in the Christian perspective are grounded in justice and shalom as expressions of God’s will. The state is understood as an instrument to uphold justice, while believers are called to demonstrate responsible citizenship through obedience to law, active participation in society, and commitment to peace and moral integrity. This study highlights the importance of integrating faith and social responsibility to contribute constructively to national harmony.